L'homme et l'hiver dans l'art au Québec: méthodes d'analyse de documents iconographiques - Lamontagne, Sophie-Laurence (Ethnologies, 1981)
AbstractSince time immemorial man has used words to fashion discourse — first oral then written — but only after having, up to a certain point, outlined in images the deeds, events, things or ideas to communicate. Although across the centuries the image has known many uses, it still remains for us an astonishing manifestation of communication through which it is important to grasp the implications of the discourse. The study of images permits the elaboration of numerous hypotheses to explicate material or spiritual culture. One of these hypotheses proposes the identification and then the explication, through iconography, of diverse phenomena of man's adaptation to daily life in the winter. In other words, it suggests that iconography projects an ethnographie discourse; that is to say, portrays acts and characteristics of the Euroquébécoise culture.